A247 VIRAL LOAD OF EPSTEIN-BARR VIRUS IN PEDIATRIC PATIENTS WITH NEW ONSET IBD AT DIAGNOSIS AND ON FOLLOW UP: AN OBSERVATIONAL STUDY - Kornitzer, G A (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Patients with Inflammatory Bowel Disease are at increased risk for complications associated with Epstein-Barr Virus, such as uncontrolled infection, colitis mimicking IBD, and lymphoproliferative disease. These complications may be due to inherent immune dysfunction or effects of immunomodulating therapies used. We have previously identified that the seroprevalence of EBV in our cohort of IBD patients at time of diagnosis was 44.2%, with prevalence stratified by age as follows: 0 to <10 years 36%, 10 to <17 years 46%, and 17 + years 50%. AIMS: Our objective is to assess the risk of EBV reactivation in this population, to determine whether patients treated with immunomodulators should be more closely monitored for EBV viral load. METHODS: Retrospective chart review was done for all patients with new-onset IBD diagnosed at CHU Sainte-Justine over a two-year period, from Jan. 2016 to Dec. 2017. Serum from time of diagnosis was retrieved from the microbiology laboratory for patients with positive EBV serology, and quantitative PCR was performed to assess viral load at diagnosis. 47 of 53 seropositive patients had available serum at time of retrieval. EBV PCR was subsequently performed on serum drawn one to two years after start of immunosuppressants. RESULTS: 53 patients were EBV positive at time of diagnosis (EBNA/VCA IgG). Two patients were IgM positive, suggesting recent or active infection. The viral load as measured by quantitative PCR on serum drawn at diagnosis was negative in all retroactively tested patients. Of the two IgM-positive patients, one had known positive quantitative PCR at time of diagnosis. PCR previously tested in clinical follow-up of two seropositive, PCR-negative patients became positive at 7 and 17 months from diagnosis, suggesting viral reactivation. Both patients had received anti-TNF’s and systemic corticosteroids. Viral loads on follow-up are to be assessed for the rest of the cohort. Overall, therapies started within 6 months of diagnosis were similar in the seropositive and seronegative groups, the majority receiving some form of immunosuppression. Within the seropositive group: 66% received corticosteroids, 32.1% Infliximab, 5.7% Adalimumab, and 5.7% Azathioprine. CONCLUSIONS: Only one patient had active EBV infection with positive PCR at time of diagnosis. All other patients had no sign of active infection based on retroactive PCR’s. While a majority of patients, regardless of EBV serology, receive immunomodulating agents, we currently do not routinely screen for seroconversion in seronegative patients, or for viral load in seropositive patients. We will be assessing viral loads after start of immunomodulation to better understand the potential impact of these agents on disease progression. FUNDING AGENCIES: None